“THE EVOLUTION OF THE ENGLISH LANGUAGE: FROM OLD ENGLISH TO MODERN ENGLISH”: “THE EVOLUTION OF THE ENGLISH LANGUAGE: FROM OLD ENGLISH TO MODERN ENGLISH” - Rakhimova, Zhibek (Журнал иностранных языков и лингвистики, 2025)
The history of the English language spans over 1,400 years, and throughout this extensive period, the language has undergone remarkable changes. These transformations were largely driven by historical events, sociopolitical factors, and the continuous interaction of English speakers with other cultures and languages. From its Germanic roots to its current status as a global lingua franca, English has evolved in response to shifts in society and communication. In this article, I will trace the key stages in the evolution of the English language, focusing on the significant developments that have defined each period.